HUBUNGAN PENGETAHUAN, SIKAP DAN TINDAKAN POLA ASUH IBU TERHADAP STATUS GIZI BATITA USIA 6-36 BULAN DI POSYANDU KASIH IBU KABUPATEN SOLOK - Anugrah Humairah (STIKes Al-Insyirah Pekanbaru, 2022)
Nutritional problems are a basic risk factor for various health problems, especially in infants and toddlers. The nutritional status of children under five needs special attention, especially by mothers. Mother's knowledge about good nutrition will certainly make the nutritional status of toddlers good too. Mother's attitude in choosing foods that are useful for their children will affect the nutritional status of toddlers. Mother's parenting in health and feeding in the first year of life is very important for toddler development. In general, this study aims to determine the relationship between knowledge, attitudes and parenting styles of mothers with the nutritional status of toddlers at Posyandu Kasih Ibu Wilayah Kerja Puskesmas Simpang Tanjung Nan Ampek Kabupaten Solok. This research is analytic with cross sectional study approach. Data collection has been carried out using questionnaires to 53 samples. The nutritional status of underweight toddlers (16.9%), mothers have low knowledge (50.9%), mothers have poor attitudes (58.5%), mothers have poor actions (58.5%), there is a significant relationship between mother's knowledge, attitudes and action with the nutritional status of toddlers aged 6-36 months at the Kasih Ibu Posyandu. Keywords : Nutrient Status, Treatment Pattern, Knowledge, Attitude, Action